Predictors of Exclusive Breastfeeding in Mothers Visiting Tabriz Health Centers in Iran: A Cross-sectional Study - Somayeh Zarei; Sakineh Mohammad-Al; Azam Mohammadi; Fatemeh Effati-Daryani; Mojgan Mirghafourvand (Mashhad University of Medical Sciences, 2022)
Background & aim: Exclusive breastfeeding for the first 6 months of life is recommended for all infants. Therefore, this study was performed to determine the predictors of exclusive breastfeeding in mothers.Methods: This cross-sectional study was conducted on 183 lactating mothers with infant aged 4 months referring to Tabriz health centers and health bases in July to October 2017. Sampling was done by a two-stage cluster random sampling method. Data were collected using the infant feeding checklist, the Iowa Infant Feeding Attitude Scale (IIFAS), and the Self-efficacy Scale. Independent t-test was used to determine the relationship between feeding attitude and breastfeeding self -efficacy. Logistic regression was used to determine the predictors of exclusive breastfeeding.Results: Mean of attitude toward breastfeeding was 55.13±5.5 (ranging 17 to 85).  Mean of breastfeeding self-efficacy was 131.8±15.5 (ranging 33 to 165). From 183 mothers who participated in the study, 72.0% reported exclusive breastfeeding. The results showed a statistically significant correlation between exclusive breastfeeding with feeding attitude (P = 0.005) and breastfeeding self-efficacy (P = 0.004). According to the logistic regression model, there was a statistically significant relationship between neutral breastfeeding attitude with positive attitude toward formula feeding (OR=16.6; P<0.001), vaginal delivery (OR=9.3; P<0.001), breastfeeding immediately after delivery (OR=6.8; P=0.006), personal experience of breastfeeding (OR=11; P=0.008) and refusal to breastfeed (OR=8.7; P=0.003). These variables led to increased frequency of exclusive breastfeeding.Conclusion: It is recommended to promote practical management to resolve breastfeeding problems as well as encouraging women for vaginal delivery and early breastfeeding.